Pengaruh Komitmen Organisasi, Personal Cost, Keseriusan Kecurangan, Dan Komitmen Profesional Terhadap Intensi Whistleblowing Dengan Insentif Whistleblowing Sebagai Variabel Moderasi - Wafi Nabilah; Harti Budi Yanti (Jurnal Kendali Akuntansi, 2024)
This study aims to analyze the effect of organizational commitment, personal cost, seriousness of fraud, and professional commitment on whistleblowing intention with whistleblowing incentives as a moderating variable. The study involved 186 respondents from employees working in ministries and employees of private offices engaged in banking, services, trade, and manufacturing industries in Jakarta. Data were collected using questionnaire techniques and analyzed using spss software with multiple regression analysis, descriptive, classical assumption tests and hypotheses. The results showed that organizational commitment has a positive effect on the intention of whistleblowing. Personal cost has no significant effect on the intention of whistleblowing. The seriousness of fraud has a positive effect on the intention to whistleblowing. Professional commitment has a positive effect on the intention to whistleblowing. Whistleblowing incentives strengthen the positive effect of organizational commitment on whistleblowing intentions. Whistleblowing incentives do not strengthen the effect of personal cost on whistleblowing intentions. Whistleblowing incentives strengthen the positive effect of fraud seriousness on whistleblowing intentions. Whistleblowing incentives do not strengthen the effect of professional commitment on whistleblowing intentions.